2022
DOI: 10.1200/jco.2022.40.6_suppl.165
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based tumor mutational burden from circulating tumor DNA and immune checkpoint inhibitors in advanced prostate cancer.

Abstract: 165 Background: A prior study of patients with advanced cancers treated with immune checkpoint inhibitors (ICI) associated improved overall survival with tissue tumor mutational burden above the 80th percentile in each histology (tTMB-H). TMB can also reliably be calculated via liquid biopsy (bTMB), and trends higher than tTMB in analogous tumors. Here, we generate a plasma-informed benchmark for bTMB-H in advanced prostate cancer and report preliminary data from an ongoing multi-institutional case series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The TMB 80th percentile differs between cancer types and has been described based on bTMB with bTMB-H for prostate cancer based on ctDNA being 13.4 mut/Mb [17]. Rauterkus et al [5] showed pembrolizumab used in mCRPC patients with bTMB ≥ 13.4 mut/Mb had disease control in 86% of patients demonstrating the ability of bTMB to predict response. However, this also included patients who had concurrent MSI-H status.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The TMB 80th percentile differs between cancer types and has been described based on bTMB with bTMB-H for prostate cancer based on ctDNA being 13.4 mut/Mb [17]. Rauterkus et al [5] showed pembrolizumab used in mCRPC patients with bTMB ≥ 13.4 mut/Mb had disease control in 86% of patients demonstrating the ability of bTMB to predict response. However, this also included patients who had concurrent MSI-H status.…”
Section: Discussionmentioning
confidence: 99%
“…The o cial companion diagnostic test for assessing tissue TMB (tTMB) and microsatellite status for pembrolizumab is FoundationOne®CDx using tumor tissue [3]. However, circulatory DNA via blood plasma (ctDNA) represents a convenient and non-invasive analysis for determining microsatellite status and blood TMB (bTMB) with bTMB values in the 80th percentile demonstrating e cacy across tumor types [4,5,6]. It remains unknown if TMB should be interpreted differently across tumor types.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations